Binding of CO2 by a Mes2PCH2CH2B(C6F5)2 Species: An Involvement of the Ground State Species in a Low‐Energy Pathway. Issue 49 (4th November 2013) - Pu, Maoping; Privalov, Timofei
<x xml:space="preserve">Abstract</x> Minimum‐energy pathway of CO2 binding by Mes2PCH2CH2B(C6F5)2 in the gas phase starting directly from the ground state was calculated. Calculations showed that there is no need to stretch the PB bond, which is the commonly considered transformation towards an "open form" that occurs before CO2 approaches the ground state conformation of complex (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>